POLITIK HUKUM DALAM PUTUSAN HAKIM - Bhakti, Teguh Satya (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2016)
A law (written law) was never full, clear and complete set of community life, so it is always lagging behind follows the development of society. To keep abreast of it, the law should always be developed in order to remain update and relevant to the times. Implementation and development of legislation going through the verdict (jurisprudence) in the judicial process. In other words, jurisprudence intended as legal development, to meet the legal needs of justice seeker. Implementation of the functions of law enforcement and justice as well as the function of legal discovery (rechtsvinding) embodied in a verdict (jurisprudence), should refer to Pancasila as the norm of fundamental state (staatsfundamentalnorm) or wisdom / genius of the national (national wisdom / national genius) and 1945 as the basic law of the state, so that the decision reflects the sense of justice of the nation and the people of Indonesia as well. It declares a political manifestation of the law in a verdict.Keywords : politics of Law, verdic